Mir-331-3p Inhibits PRRSV-2 Replication and Lung Injury by Targeting PRRSV-2 ORF1b and Porcine TNF-α - You, Xiangbin; Qu, Yilin; Zhang, Yue; Huang, Jingshu; Gao, Xiaoxiao; Huang, Chengyu; Luo, Gan; Liu, Qian; Liu, Min; Xu, Dequan (Frontiers in Immunology, 2020)
Porcine reproductive and respiratory syndrome (PRRS) caused by a single-stranded RNA virus, PRRSV, is a highly infectious respiratory disease and leads to huge economic losses to the swine industry worldwide. To investigate the role of miRNAs in the infection and lung injury induced by PRRSV, the differentially expressed miRNAs (DE-miRs) were isolated from PRRSV infected/mock-infected PAMs of Meishan, Landrace, Pietrain and Qingping pigs at 9hpi, 36hpi, and 60hpi. Mir-331-3p was the only common DE-miR of 4 pig breeds at 36hpi and one of 4 common DE-miRs of Meishan, Pietrain and Landrace pigs at 60hpi. Mir-210 was one of 7 common DE-miRs of Meishan, Pietrain and Qingping pigs at 60hpi. Mir-210 and mir-331-3p were both predicted to directly target PRRSV ORF1b, and verified by double luciferase assay. In addition, mir-331-3p could target and regulate porcine TNF-α gene, and mir-210 could target and regulate porcine STAT1 gene. Furthermore, mir-331-3p and mir-210 could both inhibit PRRSV copy number and N protein. STAT1 and TNF-α could mediate the transcriptional activation of MCP-1, VCAM-1, and ICAM-1. STAT1could also regulate the expression of TNF-α by binding to the promoter region of TNF-α. The pEGFP-N1--mir-331-3p could significantly reduce viral replication and pathological changes in PRRSV-infected piglets in vivo. Taken together, Mir-331-3p/TNF-α and mir-210/STAT1/TNF-α have significant roles in the infection and lung injury caused by PRRSV and may be promising therapeutic targets for PRRS and lung injury/inflammation.